Metabolically healthy across body mass index categories in relation to serum Klotho levels: a population-based study - Shu, Yanling; Yang, Junfan; Dou, Linfei; Wu, Mingyang (Frontiers in Endocrinology, 2025)
BackgroundMetabolic health status and body mass index (BMI) are both key predictors of aging-related diseases and premature mortality. However, the relationship between metabolically distinct phenotypes, classified by BMI categories, and serum Klotho levels—a biomarker of aging—remains poorly understood. This study aimed to investigate the association between metabolically healthy phenotypes and serum Klotho levels among middle and aged adults.MethodsA total of 11,413 participants were included in this study. Participants were categorized into phenotypes according to metabolic disorders and BMI: metabolically healthy and normal weight (MH-NW), metabolically healthy and overweight (MH-OW), metabolically healthy and obesity (MHO), metabolically unhealthy and normal weight (MU-NW), metabolically unhealthy and overweight (MU-OW), and metabolically unhealthy and obesity (MUO). Weighted multivariate linear regression models were performed to estimate the association between metabolically healthy phenotypes and Klotho levels.ResultsAfter adjusting for potential confounders, participants in the MH-OW, MU-OW, and MUO groups had significantly lower Klotho levels compared to the MH-NW group, with estimated percentage changes (95%CIs) at -5.4% (-9.2% to -1.4%), -5.0% (-8.3% to -1.5%), and -5.7% (-8.7% to -2.5%), respectively. Additionally, reduced Klotho levels were more pronounced among females with MU-OW and MUO phenotypes, showing estimated percentage changes of -6.6% (-11.1% to -1.9) and -8.4% (-12.7% to -3.8%), respectively.ConclusionThis large population-based study found that Klotho levels vary according to metabolically healthy status across BMI categories, with metabolically unhealthy phenotypes exhibiting notably lower levels. These findings highlight the influence of metabolic abnormalities and body fatness on the aging process.